Worldwide Incidence of Ocular Melanoma and Correlation With Pigmentation-Related Risk Factors - Wu, Mike; Yavuzyiğitoğlu, Serdar; Brosens, Erwin; Ramdas, Wishal D.; Kiliç, Emine (Investigative ophthalmology & visual science, 2023)
The worldwide incidence of ocular melanoma (OM), uveal melanoma (UM), and conjunctival melanoma has last been reported on 15 years ago. Recently, light iris color and four specific single-nucleotide-polymorphisms (SNPs) have been identified as a UM-risk factor. Furthermore, six iris color predicting SNPs have been discovered (IrisPlex). Interestingly, two of these (rs129138329 and rs12203592) are also UM-risk factors. We collected worldwide incidence data of OM and investigated its correlations with iris color, IrisPlex SNPs, and UM-risk SNPs.PurposeThe worldwide incidence of ocular melanoma (OM), uveal melanoma (UM), and conjunctival melanoma has last been reported on 15 years ago. Recently, light iris color and four specific single-nucleotide-polymorphisms (SNPs) have been identified as a UM-risk factor. Furthermore, six iris color predicting SNPs have been discovered (IrisPlex). Interestingly, two of these (rs129138329 and rs12203592) are also UM-risk factors. We collected worldwide incidence data of OM and investigated its correlations with iris color, IrisPlex SNPs, and UM-risk SNPs.Cases of OM, as defined by the International Classification of Diseases Oncology C69 (eye), 8720/3 to 8790/3 (malignant melanoma), and 8000 to 8005 (malignant neoplasm), between 1988 and 2012, were extracted from the Cancer Incidence in Five Continents. Incidence rates were age-standardized and their trends were analyzed with joinpoint regression and age period cohort modeling. Frequencies for each country of iris color, IrisPlex SNPs, and UM-risk SNPs were collected from the literature.MethodsCases of OM, as defined by the International Classification of Diseases Oncology C69 (eye), 8720/3 to 8790/3 (malignant melanoma), and 8000 to 8005 (malignant neoplasm), between 1988 and 2012, were extracted from the Cancer Incidence in Five Continents. Incidence rates were age-standardized and their trends were analyzed with joinpoint regression and age period cohort modeling. Frequencies for each country of iris color, IrisPlex SNPs, and UM-risk SNPs were collected from the literature.Incidence rates were generally ≥8.0 cases per million person-years in Northern Europe, Western Europe, and Oceania; 2.0 to 7.9 in North America, Eastern Europe, and Southern Europe; and <2.0 in South America, Asia, and Africa. OM incidence correlated with latitude (r = 0.77, P ≤ 0.001) and is expressed as a north-to-south decreasing gradient in Europe. SNP rs12913832 correlated with OM incidence (r = 0.83, P ≤ 0.001), blue iris color (r = 0.56, P ≤ 0.05), green iris color (r = 0.51, P ≤ 0.05), and brown iris color (r = -0.64, P ≤ 0.01). Trends were stable for most countries (28/35).ResultsIncidence rates were generally ≥8.0 cases per million person-years in Northern Europe, Western Europe, and Oceania; 2.0 to 7.9 in North America, Eastern Europe, and Southern Europe; and <2.0 in South America, Asia, and Africa. OM incidence correlated with latitude (r = 0.77, P ≤ 0.001) and is expressed as a north-to-south decreasing gradient in Europe. SNP rs12913832 correlated with OM incidence (r = 0.83, P ≤ 0.001), blue iris color (r = 0.56, P ≤ 0.05), green iris color (r = 0.51, P ≤ 0.05), and brown iris color (r = -0.64, P ≤ 0.01). Trends were stable for most countries (28/35).OM incidence is highest in populations of European ancestry and lowest in populations of Asian and African ancestry. Overall, trends are stable, and the spatial correlation among OM incidence, iris color, and rs12913832 may support the role of pigmentation-related risk factors in OM development.ConclusionsOM incidence is highest in populations of European ancestry and lowest in populations of Asian and African ancestry. Overall, trends are stable, and the spatial correlation among OM incidence, iris color, and rs12913832 may support the role of pigmentation-related risk factors in OM development.